Neoliberalism, crisis and authoritarian–ethnicist reaction: The ascendancy of the Orbán regime. (April 2019) - Fabry, Adam
This paper analyses the seemingly contradictory fusion between authoritarianism and neoliberalism in Hungary under the Orbán regime. Since coming into power in 2010 on a popular backlash against austerity, the hard-right Fidesz–KDNP government, led by Viktor Orbán, has carried out a root-and-branch transformation of Hungarian society. While officially proposing a break with neoliberalism at home and abroad, the paper argues that the Orbán regime has rather deepened it, producing a specific variety of 'authoritarian neoliberalism', which skilfully combines some of the central tenets of neoliberalism (maintenance of a balanced budget, introduction of a flat tax system and the pursuit of regressive social policies) with 'ethnicist–populist' measures that seek to co-opt, coerce or manufacture consensus among subaltern groups in society against alleged 'enemies' of the Hungarian nation. While Orbán's 'illiberal' politics have been strongly criticized by neoliberal institutions, such as the IMF and the EU, they have taken little concrete action against the Hungarian government. We argue that the reason for this is pragmatic: the Orbán regime has not only been a model for neoliberal austerity in Europe since the 2008 crisis, but also its authoritarian and xenophobic policies are not that different from other EU states.